Understanding Russianness - Alapuro, Risto, 1944-; Mustajoki, Arto S. 1948-; Pesonen, Pekka. (Routledge advances in sociology., 2012)
In today's world where other cultures are being tapped to a greater extent than ever before, the processes of mixing and matching are especially relevant in making sense of Russia. Not only do borrowing and assimilation, interaction between the familiar and the alien, constitute a venerable tradition in Russian culture, but during the two last post-Soviet decades a notable Western influence has become apparent. This book provides means for understanding Russianness in this new situation. By bringing together Russian and Western, eminent and younger scholars it provides insights both from inside and outside. By extending its perspectives to three fields - linguistics, cultural studies, and social sciences - it covers different dimensions of creative misunderstandings , hybrids, tensions and other modes of adaptation in the Russian culture. By offering concrete case studies it avoids easy stereotypes, deconstructs clichés, problematizes accepted truths, and identifies points of interaction between Russia and the West. -- Book Description.